Medical Humanities: The beginning of smallpox vaccination in the Duchy of Parma - Virdis, Raffaele (Acta Biomedica Atenei Parmensis, 2019)
Maria Luigia (Marie Louise) of Habsburg, daughter of the Austrian Emperor and, as Napoleon Bonaparte’s second wife, Empress of the French, after the defeat of the husband in 1814 was relegated to role of Duchesse of Parma, Piacenza and Guastalla. She arrived in Parma in 1816 accompanied by several Austrian army and administrative officials, which were instructing and controlling her, and, willingly, she left to them most of the political and administrative decisions. On the contrary, since the first years she was interested and wanted to take decisions in the field of public health and charity. She opened new specialized hospitals and hospices for poor people, orphans and abandoned children, and, in February of 1820, promulgated the new «Regulations of the vaccinations», an exhaustive and specific code, that was taking into consideration the times, the places, and the people who had to vaccinate or to be vaccinated. Moreover, she fixed the modalities, the incentives, the sanctions, and she also nominated a series of people who had to publicize vaccinations and to help the general population inovercoming fears, prejudices and other causes of distrust. The new dispositions increased the number of vaccinated people in the Duchy, saving it from several epidemics that appeared in the following decades in the neighboring regions (Tuscany, Lombardy). In 1831 and 1832 she issued other two ordinances in which she urged the populations and the doctors to increase the vaccinations, probably after a decrease in interest of both, and introduced new practical arrangements to simplify and to facilitate the practice, ensuring and verifying the outcome. The effectiveness of the provisions of Maria Luigia has been shown by the marked decrease in smallpox epidemics throughout her whole reign, until 1847. Meanwhile after the end of the reign, in the second part of the nineteenth century, there was an increase of epidemics, because the following governments of the Bourbons Duchy (1847-1860) and of the united Italy after 1860 were not as diligent and active on spreading vaccinations.